2009
DOI: 10.1007/s00520-008-0568-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-disclosure of cancer diagnosis: an examination of personal, medical, and psychosocial factors

Abstract: Our results underline the persistent need for delivering patient-focused health services in oncological care based on respect for the patients' right to autonomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 42 publications
0
25
0
1
Order By: Relevance
“…Previous research has reported a relationship between nondisclosure and negative patient outcomes (e.g. increased distress, unfulfilled communication, hopelessness), [21][22][23][24] the avoidance of which were, interestingly, some of the reasons for nondisclosure for some Eastern families. [25][26][27][28] Further, oncologists reported feeling themselves, a sense of lost opportunity and poor communication due to nondisclosure, suggesting that cultural training could improve their own outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported a relationship between nondisclosure and negative patient outcomes (e.g. increased distress, unfulfilled communication, hopelessness), [21][22][23][24] the avoidance of which were, interestingly, some of the reasons for nondisclosure for some Eastern families. [25][26][27][28] Further, oncologists reported feeling themselves, a sense of lost opportunity and poor communication due to nondisclosure, suggesting that cultural training could improve their own outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, it was common to avoid the word "cancer" or informing patients about their malignant disease; however, such avoiding behaviors are not approved in many countries anymore (2).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is a potentially life‐threatening disease that is considered incurable in many cultures (Kazdaglis et al ., 2010). Receiving a cancer diagnosis can be an extremely stressful event that affects patients and their families, both physically and emotionally (Widows et al ., 2005; Dégi, 2009). The issue of whether, how, and how much to disclose to patients about their disease is approached in different ways, depending on the country (Phungrassami et al ., 2003; Mystakidou et al ., 2004).…”
Section: Introductionmentioning
confidence: 99%